Internet and social media use among patients with colorectal diseases (ISMAEL): a nationwide survey. (2nd August 2020) - Sturiale, A.; Pata, F.; De Simone, V.; Pellino, G.; Campennì, P.; Moggia, E.; Manigrasso, M.; Milone, M.; Rizzo, G.; Morganti, R.; Martellucci, J.; Gallo, G.; et al.
Abstract: Aim: Social media are used daily by both healthcare workers and patients. Online platforms have the potential to provide patients with useful information, increase their engagement and potentially revolutionize the patient–physician relationship. This survey aimed to evaluate the impact of the Internet and social media (I&SM) on patients affected by colorectal and proctological diseases to define a pathway to develop an evidence‐based communications strategy. Method: A 31‐item anonymous electronic questionnaire was designed. It consisted of different sections concerning demographics and education, reason for the visit, knowledge of the diseases, frequency of I&SM use and patients' opinions about physicians' websites. Results: Over a 5‐month period, 37 centres and 105 surgeons took part in the survey, and a total of 5800 patients enrolled. Approximately half of them reported using the Internet daily, and 74.6% of the study population used it at least once per week. There was a correlation ( P < 0.001) between those who used the Internet for work and those who had knowledge of both symptoms and the likely diagnosis before consultation. Patients who used the Internet daily were more likely to request a consultation within 6 months of symptom onset ( P < 0.0001). Patients with anorectal diseases were more likely to know about their disease and symptoms before the visit ( P < 0.001). Conclusion: Colorectal patients use I&SM to look for health‐related information mainly after their medical visit. Surgeons and hospital networks should plan a tailored strategy to increase patient engagement, delivering appropriate information on social media.